2018
DOI: 10.3855/jidc.9672
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between toxoplasmosis and different types of human tumors

Abstract: Introduction: Toxoplasma gondii is an intracellular protozoan that may disrupt the traditional cell barriers against cancer, allowing the accumulation of oncogenic mutations over time. Our research aimed to explore the relationship between T. gondii infection and tumor development. Methodology: The anti-T. gondii IgG and IgM antibodies were tested for156 patients with tumors (51 with breast cancer, 20 with hepatoma, 20 with larynx carcinoma, 20 with squamous cell carcinoma of bone, 16 with lymphoma, 13 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
3
12
0
1
Order By: Relevance
“…Retinochoroiditis; Pneumonia as well as other spread basic contaminations, can in like manner be found, anyway are not as fundamental as encephalitis in low immunity patients (2) . The harm can reactivate inactive Toxoplasmosis gondii ailment during the treatment of cancer (3) . Many type of malignancies, including multiple myeloma; lymphoma and leukemia that can reactivate toxoplasmosis (2) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinochoroiditis; Pneumonia as well as other spread basic contaminations, can in like manner be found, anyway are not as fundamental as encephalitis in low immunity patients (2) . The harm can reactivate inactive Toxoplasmosis gondii ailment during the treatment of cancer (3) . Many type of malignancies, including multiple myeloma; lymphoma and leukemia that can reactivate toxoplasmosis (2) .…”
Section: Resultsmentioning
confidence: 99%
“…The incitement of the safe reaction by T. gondii or hindrance of angiogenesis may clarify the biologic premise of these perceptions. In creature, it has been demonstrated that specific parasites or parasitic mixes had the option to repress disease growth (3) . Nevertheless, in low immunity people, reactivation of the idle T. gondii bradyzoites transformed to the proliferative tachyzoite stage that can cause toxoplasmic encephalitis (TE) (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Este trabajo constata que, pese a que casi la mitad de las muestras correspondieron a mujeres, la proporción de mujeres positivas para IgG T. gondii fue significativamente mayor que la encontrada en los hombres, hallazgo concordante con otros estudios en adultos con cáncer 12,16,17 y distinto a lo encontrado en un estudio en Estados Unidos de América realizado entre 2009 y 2010, con una prevalencia mayor en hombres (p < 0,05) 18 . Estas variaciones de prevalencia entre países podrían deberse a diferencias socio-culturales y de costumbres, tales como el cuidado de las mascotas, particularmente los gatos, el cuidado del jardín, la manipulación de carne cruda o parcialmente cocida, limpieza de frutas y verduras, entre otras actividades domésticas 12,17 .…”
Section: Discussionunclassified
“…Thus, Due to the close association between T. gondii prevelance and cancer [36,37], and T. gondii prevelance and leishmaniasis [38] which are both fatal, clinicians should be more careful with toxoplasmainfected cancer or leishmanial patients receiving miltefosine. Moreover, parasitological surveys of miltefosine-receiving patients should be regularly carried out, aiming at preventing the possibility of severe accidental toxoplasmosis during therapy.…”
Section: Discussionmentioning
confidence: 99%